Valdosta Area Black Achievers In Public Service, 1988 - (:unkn) unknown (Valdosta State University Archives and Special Collection, 1988)
The calendar, dated 1988, displays photos and biographies of successful and prominent African Americans in Valdosta. These individuals would include: Ruth Kimball, Willie Houseal, Joseph "Sonny" Vickers, Bunnis C. Williams, Juanita McCrae Miller, Maceo A. Horne, Ethel Jones Greer, Claydon Hayward Barron, Jacqueline Cooper Dunbar Brown, Ernest Thomas Townsend, Minnie Anderson Martin, Alvin Payton, Sr., Reverend Willie Frank Wade, and John Saunders.
1 electronic document, PDF, 31 scanned images
Keywords: Valdosta (Ga.); Lowndes County (Ga.); African American leadership